Immunoreactivity of Intact Virions of Human Immunodeficiency Virus Type 1 (HIV-1) Reveals the Existence of Fewer HIV-1 Immunotypes than Genotypes - Nyambi, Phillipe N. (American Society for Microbiology, 2000)
In order to protect against organisms that exhibit significant genetic variation, polyvalent vaccines are needed. Given the extreme variability of human immunodeficiency virus type 1 (HIV-1), it is probable that a polyvalent vaccine will also be needed for protection from this virus. However, to understand how to construct a polyvalent vaccine, serotypes or immunotypes of HIV must be identified. In the present study, we have examined the immunologic relatedness of intact, native HIV-1 primary isolates of group M, clades A to H, with human monoclonal antibodies (MAbs) directed at epitopes in the V3, C5, and gp41 cluster I regions of the envelope glycoproteins, since these regions are well exposed on the virion surface. Multivariate analysis of the binding data revealed three immunotypes of HIV-1 and five MAb groups useful for immunotyping of the viruses. The analysis revealed that there are fewer immunotypes than genotypes of HIV and that clustering of the isolates did not correlate with either genotypes, coreceptor usage (CCR5 and CXCR4), or geographic origin of the isolates. Further analysis revealed distinct MAb groups that bound preferentially to HIV-1 isolates belonging to particular immunotypes or that bound to all three immunotypes; this demonstrates that viral immunotypes identified by mathematical analysis are indeed defined by their immunologic characteristics. In summary, these results indicate (i) that HIV-1 immunotypes can be defined, (ii) that constellations of epitopes that are conserved among isolates belonging to each individual HIV-1 immunotype exist and that these distinguish each of the immunotypes, and (iii) that there are also epitopes that are routinely shared by all immunotypes.